The Routledge anthology of British women playwrights, 1777-1843 (Routledge, Taylor & Francis Group, 2019)
"The Routledge Anthology of British Women Playwrights, 1777-1843 brings together ten eclectic plays by female dramatists and writers, to stimulate a rich discussion of women, writing, and theatre history. Ranging through tragedy, comedy, musical theatre and mixed-genre texts, this volume celebrates the breadth and experimental spirit of 18th century dramatic writing. Each play is accompanied by an introductory essay which addresses its sociopolitical and theatrical contexts, and outlines its performance and reception history. The selections included here invite teachers and their students to study particular works by authors of note, but also to consider the differences between works written for page and stage. While many of the plays included are recognizable as published dramas, they have been placed alongside textual artifacts that suggest plays or theatrical events of which no definitive record exists, as well as supplementary materials that invite teachers to engage their students in exploring women's dramatic writing in this era. Organised in chronological order, The Routledge Anthology of British Women Playwrights, 1777-1843 traces a history of women's writing across genres and styles, offering an invaluable resource to students and teachers alike"--